Differential detection and molecular characterization of multiple avian oncogenic viruses in backyard poultry of Tamil Nadu, India - PRABHU, M; MALMARUGAN, S; ANNE, N SWEETLINE; GOPAL, S; GOPAL, K; KUMAR, V; RAJESWAR, J JOHNSON (The Indian Journal of Animal Sciences, 2024)
The avian oncogenic viruses include Mareks disease virus (MDV), Avian Leukosis virus (ALV) and Reticuloendotheliosis virus (REV). All the three viruses as etiological agents of single and/or multiple oncogenic infections were reported previously in broiler and layer chickens. The present study describes the detection of these multiple oncogenic viruses by multiplex PCR from suspected samples collected from the native chicken of Tamil Nadu, a southern state of India. Out of 51 samples tested, 10 were found positive for MDV and 25 positive for ALV subgroup E and 6 samples positive for REV. Further, the representative samples were subjected to sequencing and phylogenetic analysis. The molecular characterisation of the present MDV strains showed the close proximity with strains from Tamil Nadu, Punjab, and Kerala states of India with bootstrap value of 97%. Further, the current REV strain showed close relatedness with the previously known Tamil Nadu REV isolate with bootstrap value of 66%. The ALV strain identified from the backyard poultry was found to be endogenous virus and showed close identity with ALV-E China isolate with bootstrap value of 78%.